Hidrólisis enzimática de biomasa celulosa obtenida de la cáscara de banano maduro mediante trichoderma sp. Para la obtención de bioetanol. - Japa Pauta, José Javier (2015)
In the present work the enzymatic hydrolysis degree peel banana and its later fermentation to ethanol was assessed. Main objective is to obtain bioethanol from the enzymatic hydrolysis of cellulosic biomass using Trichoderma sp.